OP0224 Th17 Cells and TFH Cells and their Cytokine Products Are Enriched in the Synovium of Rheumatoid Arthritis Patients and Correlate with Disease Activity. (10th June 2014) - Penatti, A.E.; Facciotti, F.; De Lucia, O.; Murgo, A.; Pierannunzii, L.; Marcello, T.; Abrignani, S.; Meroni, P.; Geginat, J.
Abstract : Background: Rheumatoid arthritis (RA) and osteoarthritis (OA) patients are affected by joint degradation caused by autoimmune pathology and cartilage loss, respectively. The balance between effector and regulatory T cell subsets that secrete respectively IL-17 (Th17 cells), IL-21 and BAFF (follicular helper T cells, TFH) or IL-10 (Tr1 cells and Tregs) are thought to be crucial in RA pathology, while little is known on the role of these T cell subsets in OA. Objectives: To monitor the frequency and function of T cell subsets in RA and OA patients in peripheral blood or affected tissue (synovial fluid and synovial membrane) and their cytokine products in serum and synovial fluid, and to correlate these parameters with disease activity. Methods: Blood samples from 24 clinically well-characterized RA patients, 11 OA and 25 healthy donors (HD) were included. Additionally, synovial fluid as well as synovial membranes were analysed when available. Composition of different T cell subsets according to surface marker expression and intracellular cytokine production were assessed by flow cytometry. Cytokines in serum and secreted by T cell subsets were correlated with disease activity assessed as das28 index or the presence of autoantibodies. Synovial B cell IgG production was measured in the absence and presence of helper and regulatory T cell subsets by ELISA. Results: Th17 cells were decreased in the peripheral blood of RA patients, while OA patients had surprisingly an altered ratio of CD25+Tregs and Tr1 cells in circulation. In synovial tissues Th17 cells, TFH and regulatory T cell subsets were enriched among CD4+ T cells in RA as compared to OA patients, while frequencies of Th1 cells were similar. RA patients had higher serum levels of IL-17, IL-10 and BAFF, while serum IL-21 was elevated in both RA and OA patients. Importantly, serum levels of IL-17, IL-10 and BAFF were enhanced only in patients with active RA or with detectable autoantibodies. Moreover, BAFF and IL-17 levels in synovial fluid were also higher in RA as compared to OA patients, while IL-10 concentrations were similar. B cells from synovial fluid spontaneously released high amounts of IgG in the absence of CD4+ helper T cells, and regulatory T cell subsets were unable to suppress B cell IgG production. Conclusions: Th17 cells and TFH cells accumulate in synovial tissues of RA patients, and IL-17 and BAFF both in serum and synovial fluid correlate with disease activity, suggesting a role for TFH cells and/or Th17 cells in disease progression and autoantibody production. Moreover, although regulatory T cell subsets are efficiently recruited to the synovium they seem to be functionally impaired, since they failed to suppress B cell antibody production. Interestingly, also OA patients show a peculiar modulation of T cell subsets in peripheral blood, but in contrast to RA patients only the anti-inflammatory cytokine IL-10 is expressed in the synovium. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5392